2016
DOI: 10.4103/0971-5916.193292
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology & risk factors of scrub typhus in south India

Abstract: Background & objectives:Scrub typhus is a major public health threat in South and Southeastern Asian countries including India. Understanding local patterns of disease and factors that place individuals at risk is pivotal to future preventive measures against scrub typhus. The primary aim of this study was to identify specific epidemiological and geographical factors associated with an increased risk of developing scrub typhus in this region.Methods:We mapped 709 patients from Tamil Nadu, Andhra Pradesh and Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 14 publications
5
51
0
Order By: Relevance
“…Earlier scrub typhus was considered to occur mostly in rural areas; however, now India as a whole has been shown to be endemic for it with outbreaks reported even from the metropolitans [5][6][7][8]. A retrospective study on 709 patients admitted at a tertiary care hospital in South India has identified farming, not wearing shirt at home, living in houses adjacent to bushes and shrubs as risk factors for acquiring the infection [12]. Many of our patients did not have the risk factors conventionally associated with acquiring the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier scrub typhus was considered to occur mostly in rural areas; however, now India as a whole has been shown to be endemic for it with outbreaks reported even from the metropolitans [5][6][7][8]. A retrospective study on 709 patients admitted at a tertiary care hospital in South India has identified farming, not wearing shirt at home, living in houses adjacent to bushes and shrubs as risk factors for acquiring the infection [12]. Many of our patients did not have the risk factors conventionally associated with acquiring the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Scrub typhus occurs sporadically between seasons. 12 The seasonality of spotted fever and murine typhus has not been studied. The study was conducted in all three geographic settings (urban communities, rural plain villages, and peri-forest hill villages).…”
Section: Methodsmentioning
confidence: 99%
“…The highest number of cases were reported in October, December and January in the period immediately after the Southeast and Northwest monsoon in Tamil Nadu. 4 Majority of cases of scrub typhus in our institution are also seen during the cooler months and rainy season between months of August and December. Similar finding has been reported in earlier studies.…”
Section: Discussionmentioning
confidence: 99%